EFEITOS DA LASERTERAPIA E MICROAGULHAMENTO NAS CICATRIZES DE ACNES ATRÓFICAS (Fiep Bulletin - online, 2024)
Acne scars occur as a result of deep inflammation. Inflammation in acne is a process of lymphocytes and neutrophils that affects the thinnest follicular wall of the closed comedo and, when this wall is disrupted, the leakage of irritating follicular content into the dermis leads to a variety of lesions. The absorption of thermal energy by the chromophores present in the epidermis/dermis stimulates the remodeling of the extracellular matrix, the production of collagen and elastin, reducing the inflammatory process and stimulating tissue healing in acne lesions. Microneedling stimulates collagen synthesis percutaneously, that is, through small injuries caused in the skin, initiating a repair cascade. The application of the study will be carried out with only 3 women, they will undergo a physical evaluation in person in the first session and at the end of the sessions, in the second session, laser therapy and microneedling will begin at a frequency of 1 time a week, which will last 1 hour each service . This research will aim to identify the effects of laser therapy and microneedling on atrophic acne scars in order to develop and prove that they can be efficient methods for treating it, thus promoting self-esteem and physical and emotional well-being to patients.